Speech and language practice in cognitive communicative disorder secondary to dementia: A qualitative approach - Salazar Aguayo, Andrea; Contreras Cubillos, Sebastián; Briones Rojas, César; Oyarzún Díaz, Patricia (Revista de Investigación en Logopedia, 2026)
Speech-language pathology practice with older adults includes the assessment and intervention of cognitive-communicative disorders (CCD). This scope of practice involves evaluation, diagnosis, treatment, follow-up, counseling, health promotion, prevention, and interprofessional collaboration. In Chile, the prevalence of cognitive decline in the older population has increased; however, research on speech-language pathology practices addressing CCD secondary to major neurocognitive disorder (MaNCD) remains scarce, with a predominant focus on dysphagia. The aim of this study was to describe the clinical practice of speech-language pathologists who work with older adults with CCD secondary to MaNCD, from the perspective of professionals in the Maule Region of Chile. A qualitative study with a phenomenological design and descriptive–interpretative scope was conducted, using semi-structured interviews with twelve speech-language pathologists experienced in this field. Data were organized through thematic coding using Atlas.ti software. For interpretation, both aprioristic and emergent categories were considered. Analysis was carried out through investigator triangulation. Results indicate that speech-language pathology practice is structured around four main categories: disciplinary knowledge, assessment, treatment, and other professional services. Although actions are aligned with internationally validated guidelines, the clinical approach varies significantly depending on the professional’s context and experience, resulting in heterogeneous practices adapted to local conditions. This study highlights the need to strengthen a comprehensive approach to CCD in older adults with MaNCD in real-world clinical settings.